2019
DOI: 10.1172/jci.insight.126749
|View full text |Cite|
|
Sign up to set email alerts
|

TFEB-driven lysosomal biogenesis is pivotal for PGC1α-dependent renal stress resistance

Abstract: Because injured mitochondria can accelerate cell death through the elaboration of oxidative free radicals and other mediators, it is striking that proliferator γ coactivator 1-α (PGC1α), a stimulator of increased mitochondrial abundance, protects stressed renal cells instead of potentiating injury. Here, we report that PGC1α’s induction of lysosomes via transcription factor EB (TFEB) may be pivotal for kidney protection. CRISPR and stable gene transfer showed that PGC1α-KO tubular cells were sensitized to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…In cultured renal tubular cells, overexpression of PGC1α protected against oxidant stress 48 . Our research group found that mice with global or tubule-specific knockout of the gene encoding PGC1α exhibited blunted recovery and worse renal injury following endotoxaemia, systemic cisplatin treatment or bilateral renal IRI compared with wild-type controls 47,49,50 . Conversely, mice with tubule-specific overexpression of PGC1α were protected against all three models of AKI 47,49,50 .…”
Section: Nadpmentioning
confidence: 93%
See 1 more Smart Citation
“…In cultured renal tubular cells, overexpression of PGC1α protected against oxidant stress 48 . Our research group found that mice with global or tubule-specific knockout of the gene encoding PGC1α exhibited blunted recovery and worse renal injury following endotoxaemia, systemic cisplatin treatment or bilateral renal IRI compared with wild-type controls 47,49,50 . Conversely, mice with tubule-specific overexpression of PGC1α were protected against all three models of AKI 47,49,50 .…”
Section: Nadpmentioning
confidence: 93%
“…Our research group found that mice with global or tubule-specific knockout of the gene encoding PGC1α exhibited blunted recovery and worse renal injury following endotoxaemia, systemic cisplatin treatment or bilateral renal IRI compared with wild-type controls 47,49,50 . Conversely, mice with tubule-specific overexpression of PGC1α were protected against all three models of AKI 47,49,50 . The PPARGC1A locus, which encodes PGC1α, contains an evolutionarily conserved upstream open reading frame (uORF) in the 5′ untranslated region 51 .…”
Section: Nadpmentioning
confidence: 93%
“…104 PPARGC1A is considered the master regulator of mitochondrial biogenesis, binding to a host of transcription factors (most notably PPAR-family members) to increase expression of genes that augment mitochondrial abundance, oxidative phosphorylation, and FAO. [105][106][107][108] Observations that tubular PPARGC1A can reduce the severity of AKI and accelerate functional resolution 54,57,99,109 are consistent with the high metabolic activity of PTECs. 110 Less metabolically active kidney cell types including endothelial cells 54 and podocytes 111,112 may not experience the same benefit, suggesting a cell-type specific role for PPARGC1A in the kidney.…”
Section: Discussionmentioning
confidence: 61%
“…PPAR-family members and their transcriptional co-activator PPARGC1A emerged as likely upstream regulators in our dataset, with PPARA showing increased expression at 30minutes post-reperfusion in NEVKP, and PPARA/D, RXRA/B and PPARGC1A showing significantly increased expression in NEVKP at POD3. The renoprotective effects of PPARGC1A, particularly, have been described in models of septic, 52,97 toxic, 57,98 and ischemic 54,99,100 AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation